Pelatihan Teknis “Prompt Engineering” dalam Pemanfaatan AI Deepseek untuk Meningkatkan Kemampuan Menyusun Narasi Artikel Ilmiah Mahasiswa - Rukiyanto, Bernardus Agus; Muktar, Muktar; Safar, Muh.; Darmun, Darmun; Darimis, Darimis (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to address these issues through technical training “Prompt Engineering” by utilizing DeepSeek artificial intelligence. This training is designed to improve students’ understanding in designing specific instructions (prompts) to AI, so that they are able to produce article frameworks, develop arguments, and compose technical language effectively. Through this approach, students are expected to not only master writing techniques, but also utilize AI technology as a tool to support academic productivity. The implementation method includes interactive workshops, simulations of DeepSeek usage, and assistance in compiling scientific articles based on prompt engineering. Participants consisted of 30 multidisciplinary students who were given pretests and posttests to measure improvements in their abilities before and after training. The evaluation results showed significant improvements in narrative structure, accuracy of use of technical terms, and efficiency of article preparation time. This study is expected to be an innovative training model that can be widely adapted, while strengthening students’ digital literacy in facing academic challenges in the technological era.